Creative research the theory and practice of reserach for the creative industries - Collins, Hilary (Required reading range. Module reader, 2010)
Research For The Creative Industries' explores the practices & skills required for effective research in the creative industries. The book assesses how research methodologies must be adapted to suit the creative industries, & offers a guide to the process of undertaking a research project in this context.